The Impact of Playing Online Games on the Social Personality of Children in Buano Utara Village, Huamual Belakang Subdistrict, Seram Bagian Barat Regency - Tombalisa, Syahrun Alfajrin; Pinoa, Wiclif Sephnath; Partini, Dwi (JENDELA PENGETAHUAN, 2024)
The development of information and communication technology is advancing so fast, penetrating all sectors of life. North Buano Village is currently a craze in playing online games is very rapid, so it can affect social personality, especially among children. This study aims to determine the impact of playing online games on children's social personality in North Buano Country Village, Huamual Belakang District, West Seram Regency. The type of research used is qualitative research with a descriptive approach strategy. Based on the sample criteria, in this study the informants were 20 informants. The data analysis techniques used are data collection, data reduction, data presentation and conclusions. The results showed that in North Buano Village there are positive and negative factors that encourage children to play online games, including: Helping to Socialize, Cooperation, Improve English Language Skills, Reduce Stress, Train Patience, Addiction, Lazy, Lack of Sleep, Wasteful and Eyes Become Less Healthy